Being cool is risky business: Young men’s within-peer-group status, heavy alcohol consumption and aggression in bars - Dumas, T.; Graham, Kathryn; Maxwell-Smith, M.; Wells, S. (Informa Healthcare, 2015)
Although research suggests that male peers play an important role in young men’s bar aggression, little is known about specific peer-related predictors of this behaviour. Both bar aggression and heavy alcohol consumption are associated with traditional masculinity and peer-acceptance among young men; thus, engagement in these behaviours may help young men maintain positive social standings within their male peer groups. Further, increased heavy alcohol consumption may, in turn, facilitate bar aggression. We conducted the first empirical analysis of the association between young men’s within-peer-group status and propensity to respond aggressively to provocation in bars. We also examined the mediating role of heavy episodic drinking in this relationship. In this study, male bar-going university students (N = 116; Mage = 19 years) completed self-reported measures of their within-peer-group status, frequency of heavy episodic drinking in the past month, and their likelihood to physically aggress in response to hypothetical provocation at a bar. As hypothesised, the higher participants’ within-peer-group status, the more likely they were to report that they would respond to provocation at a bar with physical aggression. Moreover, the positive association between status and bar aggression was explained by increased engagement in heavy alcohol consumption. Results suggest that future intervention efforts to prevent bar aggression and harmful drinking practices may benefit from addressing issues of status among young men.